'The sport and fun of the countryside!': dance, novelty, and cosmopolitan lifestyle in interwar rural Kenya. Issue 1 (2nd January 2019) - Bushidi, Cécile Feza
Abstract : This article illuminates new dance practices that arose in interwar rural Kenya by exploring the transformations of performance in the colonial regions of the Nyanza and Central Provinces. By emphasizing dance makers' mobility, rooted cosmopolitanism, and political awareness as modes of living, I draw attention to the lives and conditions of mobile rural dwellers as drivers of creativity in dance. Performance allowed dancers to create multiple selves, provided social gathering spaces, and shaped new forms of cosmopolitan lifeworlds that crossed identity boundaries. Staging dance developed alternative conversations with colonial structures. Performing afforded many with independent arenas of belief within which they negotiated various layers of belonging, subjectivities, and domination. Taken together, the new dances that coloured the landscapes of interwar rural Kenya formed compelling counter-narratives to colonial ideologies about African lives thought to be stuck within the confines of the traditional, the rural, and the timeless.